Ciprofloxacin degradation performances and mechanisms by the heterogeneous electro-Fenton with flocculated fermentation biochar. (1st May 2023) - Jin, Yanchao; Huang, Peiwen; Chen, Xiongjian; Li, Li-Ping; Lin, Chun-Yan; Chen, Xiao; Ding, Rui; Liu, Jianxi; Chen, Riyao
Abstract: Antibiotic fermentation residue flocculated by polymeric ferric sulfate (PFS) has been classified as a "hazardous waste" in China. In this study, it was recycled into antibiotic fermentation residue biochar (AFRB) by pyrolysis and used as a heterogeneous electro-Fenton (EF) catalyst for ciprofloxacin (CIP) degradation. The results show that PFS was reduced to Fe 0 and FeS during pyrolysis, which was beneficial for the EF process. The AFRB with mesoporous structures exhibited soft magnetic features, which were convenient for separation. CIP was completely degraded within 10 min by the AFRB-EF process at an initial concentration of 20 mg/L. Increasing the working current and catalyst dosage within a certain range could improve the degradation rate. ·OH and O2 ·- were the dominant reactive oxygen species that played critical roles for CIP degradation. The antibacterial groups of CIP have been destroyed by the heterogeneous electro-Fenton process and its toxicity was negligible. The AFRB showed satisfactory performance, even though it was recycled five times. This study provide new insights into the resourceful treatment of antibiotic fermentation residues. Graphical abstract: Image 1 Highlights: The antibiotic fermentation residue is harmlessly treated into a Fenton catalyst. Polymeric ferric sulfate was reduced to Fe 0 and FeS by the fermentation residues. O2 ·- and ·OH were the dominant ROS for ciprofloxacin degradation. The AFRB revealed efficient and stable performance during the EF process. Complete degradation was achieved within 10 min at a certain condition.